SAT0531 Matrix assisted laser desorption ionization imaging mass spectrometry applied to human osteoarthritis cartilage reveals the intra-tissue metabolic heterogeneity. (15th June 2017) - Eveque-Mourroux, M; Emans, P; Welting, T; Boonen, A; Heeren, R; Cillero-Pastor, B
Abstract : Background: Osteoarthritis (OA) is one of the most common diseases, caused by a chronic degenerative disorder of the joint. OA can be related to the metabolic syndrome or metabolic abnormalities being recently defined as a subtype of the disease 1 . Matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry (IMS) technology allows for the investigation of the bimolecular distribution of proteins, lipids or metabolites through the in situ analysis of tissue sections. In order to better understand the metabolic OA phenotype, the study of the endogenous metabolic profiles using MALDI-IMS should be considered. Objectives: The main goal of this study is to apply MALDI-IMS methodology to study the metabolic spatial distribution of cartilage and to reveal intra-tissue and inter-patient heterogeneity. Methods: Human OA cartilage was obtained from donors undergoing total knee joint replacement. Samples were heat stabilized by a stabilizer system, before being snap frozen. Cartilage punches were sectioned at 12 μm thickness in a cryostat and deposited on indium tin oxide (ITO) glass slides. 9-Aminoacridine (9AA) and N-(1-Naphthyl) Ethylenediamine DihydroChloride (NEDC) matrices were sprayed on the tissues. MALDI-MS profiling and imaging experiments were performed using different mass spectrometers. Data were analyzed by different software dedicated to mass spectrometry. Results: Results showed that 9AA and NEDC matrices were both able to extract several and different compounds. MALDI-MS/MS was employed with 9AA matrix for molecular identification, confirming for the first time the presence of several metabolites in cartilage such as adenosine triphosphate, adenosine diphosphate, uridine triphosphate or N-Acetylglucosamine. Punches from lesioned and non-lesioned areas from the same OA patient were heat stabilized and sprayed with NEDC matrix. MALDI-IMS experiments at 40-μm of spatial resolution showed a different metabolic distribution between deep and superficial areas but also between lesioned and non-lesioned regions suggesting an evidence in the existence of intra-tissue heterogeneity (figure 1 ). Conclusions: MALDI-IMS methodology is a useful technique for metabolite profiling of cartilage and could be employed to study OA patient heterogeneity. This fact will be especially relevant for OA patients suffering of metabolic syndrome. References: Zhuo, Q., et al. (2012). Metabolic syndrome meets osteoarthritis. Nat Rev Rheumatol 8(12): 729–737. Disclosure of Interest: None declared